2017
DOI: 10.1515/msp-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and effective masses of TlInSe2 under pressure

Abstract: We have studied the band structure and the band gap closure of TlInSe 2 under pressure in the range of 0 GPa to 21 GPa, by employing the first-principles method based on the density functional theory. We discuss the possible metallic transition in the tetragonal phase of TlInSe 2 crystal. Our calculation results show that the value of the pressure at the crossover from the direct to the indirect gap is found to be 8 GPa. The "semiconductor-metal" transition is determined to occur at 14 GPa. The study of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…1 The neutron diffraction patterns of TlInSe 2 show tetragonal phase stability over the whole investigated range of pressure, which well correlates with the results of calculations effect of pressure on the band structure. 12 In Fig. 2, the unit cell parameters as functions of pressure presented in the range of P = 0-3.3 GPa at room-temperature.…”
Section: Resultsmentioning
confidence: 99%
“…1 The neutron diffraction patterns of TlInSe 2 show tetragonal phase stability over the whole investigated range of pressure, which well correlates with the results of calculations effect of pressure on the band structure. 12 In Fig. 2, the unit cell parameters as functions of pressure presented in the range of P = 0-3.3 GPa at room-temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that TlInTe2 has a direct and indirect band gap energy whose energy are 1.02 eV and 1.03 eV respectively. Moreover, the reported band gap values of TlInSe2 are 1.02 eV [19], 1.10 eV [20], 1.35 eV and 1.07 eV [21]. The reported band gap values for TlInTe2 are 1.03 eV and 0.99 eV [21], 1.13 eV and 0.97 eV [22].…”
Section: Electronic Propertiesmentioning
confidence: 92%
“…Considerable research efforts have been devoted to the study of TlInSe 2 , as it is a promising material for optoelectronic applications. Theoretical investigations have employed density functional theory (DFT) calculations to investigate the electronic structure, optical characteristics, phonon properties, and thermal conductivity of TlInSe 2 [4][5][6][7]. On the experimental side, various techniques have been used to grow thin films of TlInSe 2 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%